Analisis Model TOE terhadap Faktor yang Memengaruhi Keputusan UMKM di Kota Jambi dalam Mengadopsi TikTok - Febri Yanti Lingga; Muh. Subhan; Mochammad Arief Hermawan Sutoyo (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Social media platforms like TikTok have been utilized as a means of information dissemination and digital promotion due to their ability to reach a broad, interactive audience. However, the adoption rate of technology, particularly TikTok, among Micro, Small, and Medium Enterprises (MSMEs) in Jambi City is low. This condition is influenced by limited digital literacy, lack of understanding of technology benefits, and low readiness to utilize available features. The purpose of this study is to analyze factors influencing the decision to adopt TikTok by MSMEs in Jambi City by applying the Technology-Organization-Environment (TOE) model. This study was conducted using a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method, analyzed using SmartPLS 4.0, and involving 100 MSME respondents in Jambi City. The results showed that of the three hypotheses tested, one was accepted, namely organizational factors have a positive and significant effect on TikTok adoption. In contrast, the other two hypotheses were rejected, namely technological and environmental factors do not show significant influence on the decision to adopt TikTok. These findings suggest that internal factors, such as organizational readiness and support from business owners, are the main drivers of TikTok adoption by MSMEs compared to external factors.